The effect of different heavy metals pollutants in refinery effluent on corrosion rate of carbon steel - Al-Zuraiji, Sahir M.; Hasan, Basim O.; Abdulwaheed, Ola M. (Al-Nahrain Journal for Engineering Sciences, 2023)
The presence of heavy metal pollutants in refinery effluent significantly impacts the corrosion rate of carbon steel. The focus of this research is to analyze the impact of various inorganic pollutants, including copper, vanadium, nickel, and chromium ions, on the corrosion of carbon steel across different solutions. After conducting a thorough examination of various operating conditions, including pollutant concentration (ranging from 300-3000 ppm), temperature (30-60? C), and flow velocity (0-800 rpm). Our research shows that copper ions have the highest corrosion rate, with vanadium ions being a close second. Conversely, nickel and chromium had the most negligible impact on corrosion rate and, in some instances, even exhibited corrosion inhibition effects. It was also observed that an increase in flow velocity and temperature significantly amplified the corrosion rate of the metal ions investigated.